2020
DOI: 10.3390/ijerph17010301
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Agents-Based Modeling and Simulation for Carbon Permits Trading in China: A Regional Development Perspective

Abstract: China has been actively taking actions to control carbon emissions and promoting development of a carbon market. However, there are many disadvantages in a carbon market, owing to various designs and policies still under trial and implementation. Adopting the multi-agents technique, we constructed a framework about national carbon market to estimate the effect of a different design of policy made on the GDP (Gross Domestic Product) and environment. In particular, national and regional abatement policies were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…China’s carbon market has high prices, severe volatility, poor liquidity, and poor information transparency [ 5 ]. Measuring the efficiency of the carbon market provides important insights for market participants in formulating trading strategies based on carbon prices [ 6 ]. In addition, the efficiency of the carbon market has a significant impact on certain energy issues, such as power generation, energy consumption, and the development of new energy technologies [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…China’s carbon market has high prices, severe volatility, poor liquidity, and poor information transparency [ 5 ]. Measuring the efficiency of the carbon market provides important insights for market participants in formulating trading strategies based on carbon prices [ 6 ]. In addition, the efficiency of the carbon market has a significant impact on certain energy issues, such as power generation, energy consumption, and the development of new energy technologies [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, we will continue studying these problems to revise the model that can potentially contribute to evaluation of air quality management. Recently, many researchers have applied ABM methods to study issues of carbon trading [22,33,34], and Taiwan has begun planning carbon trading system. Furthermore, we can develop a model for analyzing the impacts of other environmental policies, particularly energy policy and greenhouse gas management policy.…”
Section: Discussionmentioning
confidence: 99%
“…With carbon emission intensity as one of the control variables, the carbon trading mechanism affects both CER and economic growth, and the effect extent is diverse in different provinces [38]. Zheng et al [39] adopted a multi-agents technique and found by model simulation that the carbon trading mechanism harms the growth of GDP while reducing emission. It is recommended that in order to maintain economic stability, different regions need to set different emission restrictions.…”
Section: Influence Of Carbon Trading On Regional Sustainable Developmentmentioning
confidence: 99%